Legal regulation of cryptocurrency in the Russian Federation - M.Y. Shiminova, A.A. Vlasov, A.I. Ivanchak, (Opción, 2019)
The research is connected with tackling the issue of the expediency of giving the legal status to cryptocurrency as an alternative monetary system. Thorough research has been given to foreign experience and legal precedents with use ofcomparative-legal and sociological methodology.As a conclusion, using an alternative monetary system requires a balanced approach. When blockchain technology has become widely spread all over the world, the participants of the virtual money turnover should deal with each other on the legal basis. It calls for the working outof basic concepts and categories with regard to the use of virtual monetary units.